Dimensions of expatriates adjustment in distant subsidiaries: A field study of a sub‐Saharan African institutional distance. (11th October 2019) - Abugre, James B.; Williams, Karen; Debrah, Yaw A.
Abstract: The aim of this study is to investigate the determinants of expatriates' adjustments in distant and complex multinational subsidiaries. Using the institutional theory as a basis for expatriates' assignments in complex subsidiaries, the work employed a sequential mixed methodology of data collection. An in‐depth face‐to‐face interview with 21 senior expatriate executives and a quantitative survey of 204 expatriates working in various multinational subsidiaries in Ghana served as data for the work. Consequently, a structural equation modeling (SEM) and a content analysis were the basis of the data analysis. Findings showed host country culture plays a significant role in determining expatriate adjustment in distant subsidiaries. Findings also showed expatriates' competence in cross‐cultural communication significantly determines expatriates' adjustment in distant subsidiaries. The work recommends an intensive training of expatriates in cross‐cultural communication and host cultural values and behaviors for international assignees.